Calibration and test of the contact parameters for chopped cotton stems based on discrete element method - Liang, Rongqing; Chen, Xuegeng; Zhang, Bingcheng; Wang, Xinzhong; Kan, Za; Meng, Hewei (International Journal of Agricultural and Biological Engineering, 2022)
In view of the fact that the existing cotton stem simulation models are simplified and have a large discrepancy from the actual appearance and the contact parameters have not been calibrated. In this study, the simulation model and numerical simulation were established using the discrete element software EDEM. Then a second-order response model between contact parameters and repose angle had been constructed. The test result showed that the static friction coefficient, rolling friction coefficient, and coefficient of restitution between cotton stems were crucial factors affecting the repose angle. The determination coefficient corrected determination coefficient and p-value of the second-order response model were R2=0.959, R2adj =0.921, and p<0.0001 respectively. The error values of the comparison between the simulation test results and the corresponding physical test values were all less than 10%, which showed that the model was reliable and had high interpretation and predictability, this study can provide a certain theoretical basis and data support for the setting of contact parameters in the data simulation of cotton stem harvesting and processing, mechanically-harvested film residue crushing and film stem separation, etc.Keywords: discrete element method, cotton stem, repose angle, contact parameters, calibrationDOI: 10.25165/j.ijabe.20221505.6546Citation: Liang R Q, Chen X G, Zhang B C, Wang X Z, Kan Z, Meng H W. Calibration and test of the contact parameters for chopped cotton stems based on discrete element method. Int J Agric & Biol Eng, 2022; 15(5): 1–8.